A Single Simulated Heliox Dive Modifies Endothelial Function in the Vascular Wall of ApoE Knockout Male Rats More Than Females - Berenji Ardestani, Simin; Matchkov, Vladimir V.; Eftedal, Ingrid; Pedersen, Michael (Frontiers in Physiology, 2019)
Introduction The number of divers is rising every year, including an increasing number of aging persons with impaired endothelial function and concomitant atherosclerosis. While diving is an independent modulator of endothelial function, little is known about how diving affects already impaired endothelium. In this study, we questioned whether diving exposure leads to further damage of an already impaired endothelium. Methods A total of 5 male and 5 female ApoE knockout (KO) rats were exposed to simulated diving to an absolute pressure of 600 kPa in heliox gas (80% helium, 20% oxygen) for 1 h in a dry pressure chamber. 10 ApoE KO rats (5 males, 5 females) and 8 male Sprague-Dawley rats served as controls. Endothelial function was examined in vitro by isometric myography of pulmonary and mesenteric arteries. Lipid peroxidation in blood plasma, heart and lung tissue was used as measures of oxidative stress. Expression and phosphorylation of endothelial NO synthase were quantified by Western blot. Results and Conclusion A single simulated dive was found to induce endothelial dysfunction in the pulmonary arteries of ApoE KO rats, and this was more profound in male than female rats. Endothelial dysfunction in males was associated with changing in production or bioavailability of NO; while in female pulmonary arteries an imbalance in prostanoid signaling was observed. No effect of diving was found on mesenteric arteries from rats of either sex. Our findings suggest that changes in endothelial dysfunction were specific for pulmonary circulation. In future, human translation of these findings may suggest caution for divers who are elderly or have prior reduced endothelial function.